Developing teachers' intercultural sensitivity: Case study on a pilot course in Finnish teacher education. (October 2016) - Rissanen, Inkeri; Kuusisto, Elina; Kuusisto, Arniika
Abstract: In scholarly discussions, developing intercultural competencies, with intercultural sensitivity as their core, is an acknowledged aim of teacher education. Religion forms a foundational part in many cultures, and its prominence in the public sphere is increasing. However, educational research and practice have largely disregarded religious diversity. This paper examines how Finnish student teachers' develop intercultural sensitivity through self-reflective learning processes in a pilot course on cultures and religions in education. The results depict students' willingness to engage in self-reflection as a necessary starting point for developing ethno-relative orientation to diversity and sensitivity to religious identities. Highlights: Previous research and educational approaches have omitted religion from close scrutiny. Complementary learning processes between secular and religious citizens are needed. Sensitivity to worldviews as identity markers is central to teachers' intercultural sensitivity. Ethno-relative orientation to diversity is developed through self-reflection. Questioning the neutrality of one's own position increases empathy towards others.